The Role of Extension in Promoting Kartu Tani to Farmer Adoption Rate in Pati Regency - Ardian Ozzy Wianto; Drajat Tri Kartono; Dwiningtyas Padmaningrum (International Journal of Science and Society, 2020)
The agricultural sector plays an important role in economic growth in Indonesia. Central Java is one of the provinces contributing to the largest agricultural production in Indonesia. The role of the government in improving agricultural productivity in Indonesia is to provide facilities in the form of subsidized fertilizer to farmers by using an electronic card-based redemption innovation (Kartu Tani). Pati Regency in 2018 is one of the districts with the highest Kartu Tani users in Indonesia, although the target number of uses has not met expectations. This study aims to analyze the role of extension agents in promoting the innovation of Kartu Tani on the level of farmers' adoption of innovation in the Pati Regency. This research is quantitative research with explanatory type. The analysis technique used in this study is simple Linear Regression; The sample consists of 150 farmers who have a Kartu Tani. The results showed that the role of extension agents in promoting innovation did not significantly influence (P> 0.05) on the level of farmers' adoption of innovation in the Pati Regency. This shows that there is no influence on the role of extension agents in promoting innovation towards farmers in adopting the Kartu Tani innovation. Farmers get Kartu Tani information from fellow farmers because of the limited number and extension of instructors' time in providing information to farmers.